Tourist Satisfaction Analysis W.R.T. Tourist Destinations In Jammu And Kashmir - D. Jain; Sourav Mangoch (Elementary Education Online, 2023)
Kashmir being called as “paradise on Earth” is one of the major tourist attraction in India. Tourism industry is very much affected with perception the tourists carry with them about a destination. This study captured the perceptions of the visitors about J&K state, as a tourist destination which had ventured into tourism development since independence. The study evaluate the perceptions of visitors (tourists) towards J&K state with the broader objective of examining its alignment with the induced image and drawing some insights on the dimensions of the image perceptions related to the overall and specific characteristics of the place. SPSS19 and Factor analysis method was used to analyze the data. Factor analysis extracted three factors. Impact factor is more for “J&K Tourists Attractions (Destinations & Spots)”; followed by “J&K Culture, Traditions, Lifestyle and Hospitality’. Least is for the third factor ‘Paradise J&K’. Findings resulted in drawing conclusion that visitors do not carry the requisite level of positive perception for J&K as tourist destination in respect of eleven variables out of 37 variables studied in all three factors extracted. Importance – satisfaction matrix identified that though there are factors on which government and private players are paying lot of emphasis to satisfy tourists “Quadrant - Continued Emphasis”, but there exists some factors where they lacks. They need to pay attention to those factors as highlighted in IS matrix in Quadrant “Opportunities for Improvement”.